Itínere. - Bueno, Gustavo; Corredoira, Pilar; Garcia, Aurora; Nuñez, Ramón; de Noisy, Jean (Santiago de Compostela : CGAC (Centro Galego de Arte Contemporanea), 1994)
Abakanowicz, Magdalena ; Baselitz, Georg ; Bruskin, Grisha ; Chillida, Eduardo ; Kirkeby, Per ; Kuitca, Guillermo ; Lamazares, Anton ; Merz, Mario ; Leiro, Francisco ; Long, Richard ; Lüpertz, Markus ; Miyawaki, Aiko ; Navarro Baldeweg, Juan ; Sarmento, Julião ; Tàpies, Antoni ; Bernard, Clemente ; Chamorro, Koldo ; Ferrero, José ; Garcia Alix, Alberto ; Navarro, Rafael
biog., ind. tent., gr. tent., bibliog. p. 253-340
Spaans & Engels & Italiaans
Itinere, CGAC (Centro Galego de Arte Contemporanea) Santiago de Compostela, 12 Decembro 1994 - xaneiro - febreiro 1995
boek